Upgrading the value of anaerobic fermentation via renewable chemicals production: A sustainable integration for circular bioeconomy - Kumar, A. Naresh; Sarkar, Omprakash; Chandrasekhar, K.; Raj, Tirath; Narisetty, Vivek; Mohan, S. Venkata; Pandey, Ashok; Varjani, Sunita; Kumar, Sunil; Sharma, Pooja; Jeon, Byong-Hun; Jang, Min; et al. (Elsevier, 2021)
The single bioprocess approach has certain limitations in terms of process efficiency, product synthesis, and effective resource utilization. Integrated or combined bioprocessing maximizes resource recovery and creates a novel platform to establish sustainable biorefineries. Anaerobic fermentation (AF) is a well-established process for the transformation of organic waste into biogas; conversely, biogas CO2 separation is a challenging and cost-effective process. Biological fixation of CO2 for succinic acid (SA) mitigates CO2 separation issues and produces commercially important renewable chemicals. Additionally, utilizing digestate rich in volatile fatty acid (VFA) to produce medium-chain fatty acids (MCFAs) creates a novel integrated platform by utilizing residual organic metabolites. The present review encapsulates the advantages and limitations of AF along with biogas CO2 fixation for SA and digestate rich in VFA utilization for MCFA in a closed-loop approach. Biomethane and biohydrogen process CO2 utilization for SA production is cohesively deliberated along with the role of biohydrogen as an alternative reducing agent to augment SA yields. Similarly, MCFA production using VFA as a substrate and function of electron donors namely ethanol, lactate, and hydrogen are comprehensively discussed. A road map to establish the fermentative biorefinery approach in the framework of AF integrated sustainable bioprocess development is deliberated along with limitations and factors influencing for techno-economic analysis. The discussed integrated approach significantly contributes to promote the circular bioeconomy by establishing carbon-neutral processes in accord with sustainable development goals.
Keywords: Biogas; Biorefinery; Fatty acids; Succinic acid; CO2 sequestration; Organic waste